PERENCANAAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI MENGGUNAKAN METODE WARD AND PEPPARD PADA PT AKCAYA UTAMA PRESS (PONTIANAK POST) - Yoki Firmansyah (Jurnal Khatulistiwa Informatika, 2015)
ABSTRACTPT Akcaya Utama Press is a company concentrates on the field of mass media especially printed media with its product namely Pontianak Post where in running the bussiness process it has not yet fully applied the use of IS/IT in the company, although as we recognize today or in the future there is the need of IS/IT to develop company business. Based on this reason, in this thesis the writer plans information system strategy and information technology that can be applied by the company in order to give the profit for the company if it is applied in the future. The method used in this thesis is Ward and Peppard method as the writer’s frame of thinking while as the analysis the writer uses some analysis techniques such as SWOT Analysis, Value Chain Analysis, KPI, McFarlan Strategic Grid, Five Force porter and Pest Analysis which based on these the writer’s analyses result in several strategies whether in the form of System, technology, or information management which is applied into an application portofolio which later will be proposed to PT Akcaya Utama Press and it will be provided that if this strategy will be applied it will increase the company’s competitive excellence as the biggest printed media in Pontianak, Kalimantan Barat.Keywords: IS/IT Strategy Plan, Ward and Peppard, Application Portofolio